2010
DOI: 10.1016/j.ejvs.2009.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinaemia, Low Folate Concentrations and Methylene Tetrahydrofolate Reductase C677T Mutation in Acute Mesenteric Venous Thrombosis

Abstract: Hyper-Hcy and low serum folate levels were associated with an increased risk of AMVT. The homozygous (TT) genotype of MTHFR gene mutation may be a crucial hereditary risk factor in the development of AMVT for a Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…The most common genetic risk factors for the development of VTE include the transitions G1691A in coagulation factor V (FV) and G20210A in coagulation factor II (FII) (also known as prothrombin gene) (Rosendorff and Dorfman, 2007). The C677T polymorphism in the gene encoding the enzyme methylenetetrahydrofolate reductase (MTHFR) may contribute to the etiology of VTE; study results have been inconsistent (Nizankowska-Mogilnicka et al, 2003;Almawi et al, 2005;Torres et al, 2006;Alfirevic et al, 2010;He et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common genetic risk factors for the development of VTE include the transitions G1691A in coagulation factor V (FV) and G20210A in coagulation factor II (FII) (also known as prothrombin gene) (Rosendorff and Dorfman, 2007). The C677T polymorphism in the gene encoding the enzyme methylenetetrahydrofolate reductase (MTHFR) may contribute to the etiology of VTE; study results have been inconsistent (Nizankowska-Mogilnicka et al, 2003;Almawi et al, 2005;Torres et al, 2006;Alfirevic et al, 2010;He et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that decreased levels of serum folate are a downstream result of this protein variation. Since serum folate is required for the conversion of homocysteine to methionine, these lowered levels ultimately result in a state of hyperhomocysteinemia, a condition that favors the formation of thrombi and stems from lesion formation in the vascular endothelium and the activation of the coagulation cascade (Dionisio et al, 2010;He et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The MTHFR C677T polymorphism has a high prevalence in the general population, with the frequency of heterozygotes in patients with thrombotic disease ranging between 33.6 and 51.9% in different ethnic groups (Markus et al, 1997;Morita et al, 1998;Harmon et al, 1999;Lalouschek et al, 1999;Fujimura et al, 2000;Hanson et al, 2001;Lopaciuk et al, 2001;Wu et al, 2001;Zhang and Dai, 2001;Li et al, 2002;Marcucci et al, 2003;He et al, 2010;Alves Jacob et al, 2011). In Brazilian populations of the states of Goiás and Rio de Janeiro, this frequency has been reported around 34% (Rocha, 2009;Alves Jacob et al, 2011), while in US patients of mixed ancestry with DVT (Hanson et al, 2001), a frequency of 46% was closer to and homogeneous with that found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Any disturbance in the normal physiology of gestation, such as infectious agents (brucella abortus, neospora caninum, bovine viral diarrhea virus, leptospirosis, toxoplasma gondii and trypanosoma evansi), toxins, hormonal imbalance, vaccinations, poor nutrition, chromosomal disturbances and physical influences may lead to abortion (Anderson, 2007;Givens and Marley, 2008;Neta et al, 2009;Reiterova et al, 2009;Zhu et al, 2009). The polymorphisms of MTHFR were associated with many human diseases, especially hyperhomocysteinaemia (He et al, 2009), spontaneous abortion (Zetterberg et al, 2003), early spontaneous embryo loss (Callejon et al, 2007), and recurrent pregnancy loss (Govindaiah et al, 2009). Based on the multiple functions of MTHFR, we proposed that the polymorphisms were also associated with unexplained abortion in Chinese Holstein cattle.…”
Section: Effects Of Polymorphisms On Relative Risk Of Abortionmentioning
confidence: 99%